Pengaruh Penerapan Sistem Pengendalian Manajemen Pada Pendapatan Dan Biaya Terhadap Kinerja Keuangan Klinik Mitra Medika Rancaekek Di Masa Pandemi COVID-19 - Sagita, Melda; Hamdati, Sherien Leni; Noerwulantari, Anoegrah; Hasyim, Muhammad Ardi Nupi (JURNAL ADMINISTRASI & MANAJEMEN, 2021)
Mitra Medika Clinic is a company engaged in outpatient general health. Mitra Medika Clinic has not managed a good management system in measuring company performance from the aspect of financial statements.  The author aims to measure the financial performance of Mitra Medika Rancaekek Clinic by implementing a management system appropriate to the conditions during a pandemic.  By using quantitative methods, researchers compare financial reports from year to year and the application of good financial management from several indicators.  Then the conclusions are obtained: (1) Responsibilities that are able to fulfill their responsibilities to financial institutions and financial reports.  (2) Ability to fulfill obligations, in fulfilling company obligations to pay salaries and be able to meet the operational needs of the clinic.  (3) Employee honesty by measuring honesty in making financial reports.  (4) The effectiveness and efficiency of the company is measured by the level of other indicators so as to produce a high level of effectiveness and efficiency.  (5) Management control of employees in carrying out the job description.Keyword :Financial Performance, Scala likert, Mitra Medika Clinic